The enhanced D-glucose uptake in brush border membrane vesicles by 2,6-di-O-methyl-β-cyclodextrin - Kunio Nakanishi; Masatoshi Nishi; Tohru Marukawa; Tanekazu Nadai (ՀՀ ԳԱԱ հրատ.)
D-glucose uptake in jejunal brush-border membrane vesicles(BBMV)isolated from rates, investigated by a filtration method was found to be significantly elevated in 2 mM 2,6-di-O-methyl-β-cyclodextrin (DM-CD)treated BBMV compared to control BBMV.
Keywords: Biology; Biochemistry; Pharmacology